PENGARUH PEMERINTAH DESA DAN PARTISIPASI MASYARAKAT TERHADAP PERENCANAAN PEMBANGUNAN DI DESA SUMPANG MANGO KECAMATAN PITU RIAWA KABUPATEN SIDENRENG RAPPANG - Nurmalasari Sofyan (PRAJA: Jurnal Ilmiah Pemerintahan, 2018)
Abstract The purpose of research is to determine the effect of the village administration over planning in the Village District of Pitu Riawa Sumpang Mango Sidenreng Rappang, to determine the influence of public participation in the planning of development in the Village District of Pitu Riawa Sumpang Mango Sidenreng Rappang. The study population was the head of the family in the village of Mango districts Sumpang Pitu Riawa Sidenreng Rappang totaling 559 households, while the sample is numbered 85 KK.Teknik collecting data in this research is to use observation techniques, interviews, Library Studies, and Questionnaires. The collected data was then analyzed using frequency tables and percentages. The results of this study indicate that the indicator government influence Sumpang Mango Village District of Pitu Riawa Sidenreng Rappang with a value of 68.5% an effect category, community participation Sumpang Mango Village District of Pitu Riawa Sidenreng with a value of 69.75% Rappang influential categories, indicators of development planning at Sumpang Mango Village District of Pitu Riawa Sidenreng Rappang with a value of 67.8% with effect category.